CRIMINALOGICAL PRINCIPLES OF COMBATING CRIMINAL ACTIVITY OF MINORS IN CYBERSPACE IN THE CONTEXT OF THE PROBLEM OF INVOLVEMENT OF MINORS IN SUBVERSIVE ACTIVITIES AGAINST UKRAINE (Bulletin of criminological association of Ukraine, 2024)
The article is devoted to the problem of combating criminality of minors in cyberspace in the context of their involvement in subversive activities against Ukraine. Representatives of the aggressor state, the Russian Federation, resort to all possible methods of waging war, including involving Ukrainian children in subversive, terrorist activities by recruiting them in cyberspace. The need to intensify preventive measures, strengthen cyber hygiene among minors, and establish effective operational control over the aggressor state's attempts to expand its agent network in Ukraine is emphasized. Special attention is required to reform the activities of the juvenile prevention units of the National Police towards obtaining powers to conduct operational and investigative activities, and creating cybersecurity sectors in their structure. Preventing crimes in cyberspace requires a comprehensive strategy: legal education, technical literacy, psychological support for adolescents and effective interaction between educational institutions, parents, and law enforcement agencies. Only by joining forces can young people be protected from criminal influence and prevent the loss of their future.
Keywords: cybercrime; cyberspace; recruitment; involvement of minors in illegal activities; cybersecurity; terrorist attack; sabotage; war; combating crime